2011
DOI: 10.1016/j.jmaa.2011.01.045
|View full text |Cite
|
Sign up to set email alerts
|

On the decay of solutions for porous-elastic systems with history

Abstract: In this paper we study the asymptotic behavior to an one-dimensional porous-elasticity problem with history. We show the lack of exponential stability when the porous dissipation or the elastic dissipation is absent. And we show the lack of analyticity and exponential stability when the porous viscosity and the elastic dissipation are present.Peer ReviewedPostprint (published version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…Pamplona et al [15] proved that when the dissipation mechanisms are of rate type the solutions are analytic. Soufyane [19], Soufyane et al [20,21] and Pamplona et al [16] showed several situations with more than one dissipative mechanism where the exponential decay holds. Let us also mention that Muñoz-Rivera and Quintanilla [13] obtained polynomial rates of decay form for some problems when the decay is not of exponential type.…”
Section: Microthermal Effect Viscoporous Effectmentioning
confidence: 99%
“…Pamplona et al [15] proved that when the dissipation mechanisms are of rate type the solutions are analytic. Soufyane [19], Soufyane et al [20,21] and Pamplona et al [16] showed several situations with more than one dissipative mechanism where the exponential decay holds. Let us also mention that Muñoz-Rivera and Quintanilla [13] obtained polynomial rates of decay form for some problems when the decay is not of exponential type.…”
Section: Microthermal Effect Viscoporous Effectmentioning
confidence: 99%
“…There is in the literature a huge quantity of publications analyzing this FIGURE 1 A fairy cake and a piece of travertine theory. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] It has been applying to geological materials such as rocks or soils as well as to manufactured materials such as ceramics or pressed powders.…”
Section: Introductionmentioning
confidence: 99%
“…The author proved the slow decay of the solutions with respect to the time for elastic-porous materials when there is only one dissipation mechanism in the system: the viscoporosity. After that, a lot of works have been developed to clarify the behavior of the solutions (exponential decay, slow decay, impossibility of localization and/or analyticity) for solids with voids [4,5,11,12,15,16,18,19,20,23,22,24,26,27,28,33], for non-simple materials [10,29] or for mixtures of elastic solids [1,2,3,31,32]. Nevertheless, few attention has been paid up to now to micropolar elastic solids.…”
Section: Introductionmentioning
confidence: 99%